Reduced Glutathione Protects Subcellular Compartments From Pb-Induced ROS Injury in Leaves and Roots of Upland Cotton (Gossypium hirsutum L.) - Khan, Mumtaz; Samrana, Samrana; Zhang, Yi; Malik, Zaffar; Khan, Muhammad Daud; Zhu, Shuijin (Frontiers in Plant Science, 2020)
To test the multifarious role of reduced glutathione (GSH) in alleviating Pb-toxicity, upland cotton seedlings were grown in growth mediums containing lead (Pb 500 µM), GSH (50 µM) and GSH + Pb (50 µM + 500 µM). Lead exposure exacerbated H2O2, OH• levels and lipid peroxidation (MDA), and decreased the activities of CAT and APX in the terminal and median leaves. However, in primary and secondary roots, CAT activity was increased but APX decreased. Similarly, POD and SOD activities were enhanced in median leaves but a declining trend was observed in terminal leaves, primary roots and secondary roots. GR activity, AsA contents and GSH concentrations were increased in all parts except AsA in median leaves. Transmission electron micrographs of Pb-treated plants revealed deformed cell wall and cell membrane, disfigured chloroplasts and irregularly-shaped mitochondria in terminal and median leaves. Similarly, Pb also disrupted root ultramorphology by inducing collapse of membrane-bound compartments and rendering the clear identification of cell organelles difficult. External GSH re-established leaf and root ultramorphology by stabilizing cell membranes, stimulating formation of multivesicular body vesicles, and by maintaining structural integrity of other organelles. Evidently, GSH played major alleviatory role against Pb toxicity in upland cotton.